Seven-O'clock: a new distributed GVT algorithm using network atomic operations. (22nd September 2009) - Bauer Jr., D.W.; Carothers, C.D.
In this paper we introduce a new concept, Network Atomic Operations (NAOs) to create a zero-cost consistent cut. Using NAOs, we define a wall clock time driven Global Virtual Time (GVT) algorithm called The Seven O'clock GVT algorithm that is an extension of Fujimoto's shared memory GVT algorithm. Using this new GVT algorithm, we report good optimistic parallel performance on a cluster of Itanium-II quad processor systems as well as a dated cluster of 40 dual Pentium III systems for both benchmark applications such as PHOLD and real-world applications such as a large-scale TCP/IP internet model. In some cases, super-linear speedup is observed. The Seven O'clock GVT algorithm greatly simplifies processor synchronisation by creating a zero-cost 'consistent cut' across the distributed simulation.